Spatio-temporal growth of garlic and onion crops in Gujarat - R L Shiynai, N J Ardeshna, (Journal of Spices and Aromatic Crops, 2014)
The growth in area, production and yield of onion and garlic in different districts of Gujarat was studied. The secondary data for the period from 1990–91 to 2007–08 was collected and analyzed. The annual area, production and productivity of onion significantly increased at the rate of 6.50%, 9.96% and 0.68%, respectively. In case of garlic, the annual growth was 2.98%, 4.61% and 1.52%, respectively.